On the quality of quantity and the quantity of quality - Andrey V. Belotserkovsky (Moscow Polytechnic University, 2022)
On April 10, 2013, Tver State University hosted a webinar where experts from the Russian Rector's Union and the Agency of strategic initiatives discussed prospects of macro-regulation in higher education. Some considerations on the scope of discussed matters are given and the proposals are made.